ISOMORPHIC TEST OF NEWTON’S THIRD LAW FOR INVESTIGATING STUDENTS’ SCIENTIFIC AND REPRESENTATIONAL CONSISTENCY - Mansyur, Jusman; Darsikin, Darsikin; Hidayat, Syarif (Jurnal Materi dan Pembelajaran Fisika, 2014)
We have developed a set of isomorphic test for investigating scientific and representational consistency in the context of Newton?s Third Law. The test consisted of 30 multiple-choice items concerning five central force contexts: gravitation, electrostatics, magnetic, pushing, and crashing (impulse force). The test items were designed using various representations (i.e., verbal, diagram/vectorial and graphical). Before we conducted try out, test draft was reviewed by two physics content and evaluation experts for knowing appropriateness of concepts and isomorphic aspect of the test. We provide some evidence for analyses of the test based on the classical test theory. The limitation of the test is presented in this paper. Keywords: isomorphic test, Newton?s third law, scientific consistency, representational consistency